Time-motion analysis and physiological responses of small-sided team handball games in youth male players: Influence of player number - Belka, J.; Hulka, K.; Safar, M.; Duskova, l.; Weisser, R.; Riedel, V. (Acta Gymnica, 2016)
Background: Effective training depends on knowledge of a sport's requirements. Small-sided games (SSG) are a spontaneous form of specific training, where exercise intensity can be manipulated mainly by modifying external factors. In SSG the players develop technical and tactical skills in the similar situations, such as during a match and can also develop their physical skills.